Hepatic Lobectomy-Case Report of Two Patients, Performed at Chittagong Medical College Hospital - Ali, SM Ashraf; Hussain, Md Margub (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Lobectomy of liver is indicated for different conditions; mainly malignancy and trauma. Though it is highly specialized operation and preferably be performed in specialized tertiary center, sometime a general surgeon may not be in a position to avoid the surgery due to very low socioeconomic condition or to tackle emergency traumatic condition. Two case report of Lobectomy of liver; right lobectomy for hepatocellular carcinoma, and left lobectomy for left lobe big cyst and multiple stones in it were performed at Chittagong Medical College Hospital utilizing the existing facilities. Both patients recovered uneventfully. Case I expired after two month and fourteen day, Case II leading a pain free cheerful normal life. Experience of management of these two cases of resection of liver is recorded at Chittagong Medical College Hospital. DOI: 10.3329/jbcps.v26i3.4201 J Bangladesh Coll Phys Surg 2008; 26: 153-157